1984
DOI: 10.1128/jcm.20.6.1053-1059.1984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the AutoMicrobic system for identification and susceptibility testing of gram-negative bacilli

Abstract: The AutoMicrobic system (AMS) (Vitek Systems, Inc., Hazelwood, Mo.) was compared with the API-20E system for the identification of gram-negative bacilli by using 380 stock clinical isolates and 377 immediately encountered fresh clinical isolates. For the stock isolates, with Enterobacteriaceae-Plus Biochemical Cards and automated interpretation, 364 (95.8%) were in agreement to the species level. For the fresh clinical isolates, agreement at the genus and species levels was 89.7 and 85.9%, respectively, when E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…More accurate and reliable methods with which to rapidly identify these organisms need to be developed. Some studies on the reliability of automated systems have shown good results, but insofar as the H. alvei strains are concerned, only small numbers were evaluated (34,36,37), with the unique exception of Kelly et al (12), who, using 38 Hafnia alvei strains, obtained results similar (92%) to those in our study.…”
supporting
confidence: 74%
“…More accurate and reliable methods with which to rapidly identify these organisms need to be developed. Some studies on the reliability of automated systems have shown good results, but insofar as the H. alvei strains are concerned, only small numbers were evaluated (34,36,37), with the unique exception of Kelly et al (12), who, using 38 Hafnia alvei strains, obtained results similar (92%) to those in our study.…”
supporting
confidence: 74%
“…When a life-threatening infection is suspected, the important problems are the rapid detection of a pathogen, its identification, and susceptibility testing. A few rapid systems, manual or automated ones, have been marketed and evaluated during the last 10 years (6,8,10,16,17,20). However, all of these systems usually need isolated colonies to start with, a condition which requires at least an overnight incubation of the clinical specimen.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of the AMS GNI, the number of NFGNB species or groups of species this system was capable of identifying increased from 7 to 30 (35). Although one investigator (38) has utilized the AMS GNI card to test all isolates whose identification by EBC-Plus differed from the reference technique, our study is the first to compare the AMS GNI card directly with a standard reference method in the identification of a balanced spectrum of NFGNB. We found the accuracy of the card to be high.…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly interested in evaluating the ability of the new system to identify NFGNB. Five previous groups of investigators (5,6,17,33,38) have reported on the usefulness of the older EBC-Plus card in the identification of this group of organisms. One (38) utilized the GNI card to test isolates whose identification with the EBC-Plus card differed from that obtained by a reference method.…”
mentioning
confidence: 99%